2002
DOI: 10.1002/jmv.10269
|View full text |Cite
|
Sign up to set email alerts
|

Replication capacity, biological phenotype, and drug resistance of HIV strains isolated from patients failing antiretroviral therapy

Abstract: The fitness of human immunodeficiency virus (HIV) in vivo depends on the interaction of a multitude of viral and host factors. The aim of this study was to analyze the biological phenotype and the intrinsic capacity of the HIV isolates with drug-resistance mutations to replicate efficiently in the absence of drugs. An open label multicenter cross-sectional study was undertaken on 28 HIV-infected patients failing antiretroviral treatment. The subjects were studied for CD4+ cell count, HIV viral load, syncytium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…Clinical trials have shown that HIV-1 replication fitness may play an important role in the outcome of disease (4,17,19,20), and reliable assays are needed to determine relative viral fitness in a heterogeneous population of viruses. Several investigators have used a dye-labeled primer system with automated DNA sequencer to measure the replication fitness of viruses by comparing the peak heights of two viruses at a single locus in the RT or protease genes (7,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that HIV-1 replication fitness may play an important role in the outcome of disease (4,17,19,20), and reliable assays are needed to determine relative viral fitness in a heterogeneous population of viruses. Several investigators have used a dye-labeled primer system with automated DNA sequencer to measure the replication fitness of viruses by comparing the peak heights of two viruses at a single locus in the RT or protease genes (7,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that subjects with primary HIV infections had a high prevalence of transmission of HIV-resistant strains (2, 9) and of NNRTIresistant isolates (6). A possible explanation of these findings is that HIV-1 strains with the primary mutations related to NNRTI resistance (6) show no significant difference in terms of replication capacity with respect to the wild-type virus. Therefore, a sustained viral fitness could explain the transmission of drug-resistant virus and the presence of the same mutational pattern in different compartments.…”
mentioning
confidence: 97%
“…DNA was extracted from 3 ϫ 10 6 PBMCs with a High Pure PCR template preparation kit (Roche Diagnostics GmbH, Mannheim, Germany).…”
mentioning
confidence: 99%
“…However, the V75I mutation, in combination with the Q151M complex, causes high level resistance to all NRTIs [16] while the K101Q has been identified to have a clinically significant impact on NNRTI activity [17].…”
Section: Discussionmentioning
confidence: 99%